Influence of Work Discipline and Work Environment on Employee Performance at PT Sentra Agroprima Lestari - Kirana, Fitri (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
Employees are vital to business operations, especially when it comes to time management, work discipline and work environment. The aim of this research is to examine how the work environment and work discipline influence employee performance. PT employees. The Surabaya Agroprima Lestari Center is the subject of research. This research applies quantitative research methods as its methodology. Partial Least Square (PLS) analysis was applied, along with validity and reliability checks. Research findings show that employee performance was directly and positive significantly influenced by work discipline. Employee performance is directly and positive significantly influenced by the workplace.